ChemInform Abstract: Bright Coppertunities: Multinuclear CuI Complexes with N—P Ligands and Their Applications. Issue 31 (5th August 2014) - Wallesch, Manuela; Volz, Daniel; Zink, Daniel M.; Schepers, Ute; Nieger, Martin; Baumann, Thomas; Braese, Stefan
Abstract Review: [46 refs.